Outcomes of Second-stage Reimplantation After Modular Knee Arthrodesis for Periprosthetic Joint Infection. (11th August 2022) - Stavrakis, Alexandra; Mayer, Erik N.; Devana, Sai; Chowdhry, Madhav; Dipane, Matthew; McPherson, Edward
Abstract : Background: Modular knee arthrodesis (MKU) is a salvage treatment for recurrent periprosthetic joint infection (PJI) or PJI associated with notable bone loss. Reimplantation endoprosthetic reconstruction (REI) is an option in patients with MKU who have PJI clearance but are not satisfied with pain or functional outcomes with MKU. The purpose of this study was to evaluate the outcomes of MKU to REI conversion. Methods: This was a single-center retrospective cohort study of 56 patients who underwent MKU to REI from 2010 to 2019. All patients were staged according to the McPherson staging system. An infecting organism was documented based on pre-MKU aspiration or intraoperative cultures at the time of MKU. Rate ratios were calculated for relevant patient factors. Rate ratios were calculated using Poisson regression with a log link. Results: The mean REI patient age was 67 years, most of the patients were McPherson B hosts (62.5%) with a type 2 (46.4%) or type 3 (51.8%) limb score, and all PJI were chronic. The most common infecting organisms at the time of MKU were Staphylococcus epidermidis (23.2%) and Staphylococcus aureus (23.2%, MSSA 14.3%, MRSA 8.9%). The mean time from MKU to REI was 220 days. An 8.9% REI index hospitalization complication rate and a 21.4% overall complication rate (excluding reinfection) were observed. Sixty-seven percent of the patients remained infection-free at an average follow-up of 37 months, among those there was 96.4% implant survivorship. No notable association was observed between index PJI organism or McPherson staging and REI failure secondary to PJI. Discussion: Approximately two thirds of patients who undergo conversion from MKU to REI have infection-free survival at the midterm follow-up. An index infecting organism and a McPherson host type do not seem to be markedly associated with reinfection risk. These findings help guide expectations of PJI MKU conversion to REI.